Controle e participação nas novas políticas sociais: o caso Pró-Social - Maciel, Tadeu Morato (2011)
From the 1980s, the Brazilian social policies assumed new features that enable more efficient management of programs and their beneficiaries. The current democratic society establishes monitorings of social policies and implements a constant control, verifying the achievement of desired results. Among the new elements that are redefining it, there are the decentralization of actions, focalisation of target public, income transfer programs, improvement of management through joint action, the appropriation of new information and communication technologies, integration of information in data banks and encouragement of citizen participation. This dissertation examines the various elements that compose the Pro-Social, implemented by the Government of Sao Paulo, for evaluation and monitoring of social programs and their beneficiaries by the use of the database, which promotes the integrated management of decentralized social projects and allows the construction of social indicators that measure the effectiveness of actions. It aims to point out the conditioners of new social policies implemented in recent years and how they are inserted in Pro-Social, activating new devices to government of population. Using concepts such as biopolitics and disciplinary society, by Michel Foucault, and society of control, by Gilles Deleuze, we locate these social policies in the transition of their applicability. From the discussion of Pro-social, was possible to situate disciplinary and biopolitical elements linked to devices that allow a quick and effective control, forward the new flowing relations in society of control. Besides the data monitoring looking to identify who will or will not be entitled to receive benefits, these devices permit greater popular participation in life management